Expression of high-abundance proteins in sera of patients with endometrial and cervical cancers: analysis using 2-DE with silver staining and lectin detection methods - Abdul-Rahman, P.S.; Lim, B.K.; Hashim, Onn Haji (2007)
The expression of high-abundance serum proteins in newly diagnosed patients with endometrial adenocarcinoma (EACa), squarnous cell cervical carcinoma (SCCa) and cervical adenocarcinorna (ACCa), relative to control female subjects, was analyzed by subjecting serum samples to 2-DE followed by image analysis of the silver-stained protein profiles. The three cohorts of cancer patients demonstrated different altered expression of serum high-abundance proteins compared to negative control women. Tl-ie expression of alpha(1)-antitrypsin, alpha(1)-B glycoprotein, cleaved high-molecular-weight kininogen (light chain) and antithrombin III were consistently altered in all the patients. However, clusterin was upregulated only in the patients with EACa, while those with SCCa and ACCa were typically characterized by the upregulated expression of zinc alpha-2-glycoprotein. The aberrant expression of selective serum proteins in the various cohorts of cancer patients was validated by competitive ELISA as well as by lectin detection. Analysis by using the charnpedak galactose binding lectin further highlighted an unidentified protein that may be differently glycosylated in the sera of the EACa patients that were studied.